Embedding Sustainability in Landscape Architecture Education: Assessing the Needs of the Malaysian Industry - Mohd Ali, Nurul Hidayah; Che' Rus, Ridzwan; Mohd Noor, Azlin Iryani (EDUCATUM Journal of Social Sciences, 2025)
This study assesses the need to embed sustainability elements into landscape architecture education in Malaysia, harmonising with industry demands and the Sustainable Development Goals (SDGs). Despite its relatively recent establishment in Malaysia, landscape architecture is experiencing significant growth, necessitating the integration of sustainable development principles into its educational framework. Using the Nominal Group Technique (NGT) to gather insights from seven landscape industry experts, the study identifies a strong consensus on the relevance of sustainability in landscape architecture. The findings indicate a unanimous agreement on the need for graduates to possess sustainability skills, emphasising the integration of Education for Sustainable Development (ESD) introduced by UNESCO. Although the present understanding of ESD among industry personnel is relatively excellent, there is room for development, mainly through greater collaboration between academia and industry. Therefore, this study proposes the revision and enhancement of existing curricula to integrate sustainable aspects relevant to the Malaysian context. The essential need for a comprehensive educational framework is stressed, ensuring that landscape architecture graduates are well-prepared to meet industry expectations and contribute to the SDGs.